Association of thymidylate synthase and hypoxia inducible factor-1alpha DNA polymorphisms with pancreatic cancer - Ruiz-Tovar Polo, Jaime; Fernández Contreras, María Encarnación; Martín Pérez, E.; Gamallo, C. (My University, 2012)
Background. Thymidylate synthase and hypoxia inducible factor-1¿ play a central role in the control of tumor progression. In the present study, we investigated the effect of three DNA polymorphisms within the thymidylate synthase gene and two within hypoxia inducible factor-1¿ on the prognosis of pancreatic cancer. Patients and methods. A retrospective study was performed in 59 patients diagnosed with invasive ductal adenocarcinoma of the pancreas and 159 healthy volunteers. The studied DNA polymorphisms were a variable tandem repeat of 28 bp (rs45445694), a G/C single nucleotide polymorphism (rs34743033), and a deletion of 6 bp (ins1494del 6bp; rs34489327) within the thymidylate synthase gene and C1772T and G1790A single nucleotide polymorphisms within hypoxia inducible factor-1¿ (rs11549465 and rs11549467, respectively). Variable tandem repeats were determined by specific polymerase chain reaction, whereas thymidylate synthase single nucleotide polymorphism G/C, ins1494del 6pb, and hypoxia inducible factor-1¿ polymorphisms were identified by polymerase chain reaction and RFLP. Thymidylate synthase and hypoxia inducible factor-1¿ genotype distributions in patients and healthy volunteers were determined. The impact of the polymorphisms on clinico-pathological variables, including survival, was also studied. Results. The frequency of carriers of the variant del6bp allele was significantly higher among patients (70.0% vs 51.0% of healthy donors, P = 0.02); 42% of male patients were homozygous 2R/2R vs 13.6% of females (P = 0.03), but differences regarding gender were not observed among healthy volunteers. Concerning hypoxia inducible factor-1¿ C1772T and G1790A single nucleotide polymorphisms, the rates of variant T/T and A/A homozygous genotypes were significantly elevated among patients (18.6% vs 5.3%, P = 0.001, and 5.1% vs none, P = 0.021 respectively). Conclusions. In our study, the variant del14946bp allele within the thymidylate synthase gene, and TT and AA genotypes of C1772T and G1790A hypoxia inducible factor-1¿ single nucleotide polymorphisms were associated with the development of pancreatic cancer. The 2R/2R genotype of variable tandem repeat thymidylate synthase polymorphism might be a risk factor for pancreatic cancer in males. © Il Pensiero Scientifico Editore.